2021
DOI: 10.1111/are.15253
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mealworms (Tenebrio molitor) meal as an alternative protein source for narrow‐clawed crayfish (Pontastacus leptodactylus) juveniles

Abstract: An eighty‐day feeding study was performed to investigate the effects of mealworm meal (Tenebrio molitor) on the growth, survival and moulting frequency of juvenile Narrow‐clawed crayfish (Pontastacus leptodactylus). Three dietary treatment groups with triplicate were fed with a fish meal‐based without MW (control diet: MW0), two diets with 50% (MW50) and 100% (Mw100) of fish meal substitution with MW respectively. P. leptodactylus juveniles (11.0 ± 0.05 mm, mean ±SE and 0.011 ± 0.002 g, mean ±SE) were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
2
12
0
Order By: Relevance
“…Furthermore, the analysis included the whole body, which means that exoskeleton was included, probably resulting in increased ash content. It is worth mentioning that Mazlum et al (Mazlum et al, 2021) using dietary T. molitor did not find significant alteration of the ash content of P. leptodactylus juveniles.…”
Section: Effect Of Hm Inclusion On Body Composition and Fatty Acid Pr...mentioning
confidence: 80%
See 2 more Smart Citations
“…Furthermore, the analysis included the whole body, which means that exoskeleton was included, probably resulting in increased ash content. It is worth mentioning that Mazlum et al (Mazlum et al, 2021) using dietary T. molitor did not find significant alteration of the ash content of P. leptodactylus juveniles.…”
Section: Effect Of Hm Inclusion On Body Composition and Fatty Acid Pr...mentioning
confidence: 80%
“…Most of the published studies using H. illucen s meal for fishmeal replacement have been conducted majorly in farmed fish species such as rainbow trout ( Stadtlander et al, 2017 ), Atlantic salmon ( Li et al, 2020 ), European sea bass ( Magalhães et al, 2017 ), gilthead seabream ( Karapanagiotidis et al, 2023 ), African catfish ( Fawole et al, 2020 ), Nile tilapia ( Tippayadara et al, 2021 ) and yellow catfish ( Xiao et al, 2018 ), and only few in crustaceans such as pacific white shrimp ( Cummins et al, 2017 ) and red claw crayfish ( Wang et al, 2022 ). For P. leptodactylus , Mazlum et al (2021) evaluated the use of Tenebrio molitor and reported that a dietary inclusion level of 13.5%, representing 50% of fishmeal replacement, was successful in terms of growth performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aforementioned species, BSF improved various growth parameters as well as the immune response to some diseases affecting aquatic species. Also, TM has shown positive results when utilized in the diets of many aquatic species, such as yellow catfish ( Su et al., 2017 ), gilthead seabream ( Fabrikov et al., 2021 ), largemouth bass ( Micropterus salmoides ) ( Su et al., 2022 ), seabass ( Dicentrarchuss labrax ) ( Reyes et al., 2020 ), narrow-clawed crayfish ( Pontastacus leptodactylus ) ( Mazlum et al., 2021 ), olive flounder ( Paralichthys olivaceus ) ( Jeong et al., 2021 ), black porgy ( Acanthopagrus schlegelii ) ( Jeong et al, 2022 ) and rainbow trout ( Su et al., 2017 ; Melenchón et al., 2021 ). Furthermore, TM has a relatively high nutritional value as well as being a rich source of essential amino acids (methionine), lipids and fatty acids, that vary based on the developmental stage of the larvae ( Shafique et al., 2021 ).…”
Section: Insect Species Utilized In Aquafeedmentioning
confidence: 99%
“…(2018) Meal Narrow-clawed crayfish ( Pontastacus leptodactylus ) 0.011 ± 0.002 80 d 50 Improved weight gain, specific growth rate, protein efficiency ratio, apparent net protein utilization, molting frequency, and feed conservation ratio, but lower survival rate as compared to the other diet groups. Also improved protein and lipid content of the whole body Mazlum et al. (2021) Meal Black porgy, ( Acanthopagrus schlegelii ) 6.43 ± 0.00 12 wk 60 Improved serum lysozyme activity and upregulation of antioxidant enzyme-related genes but with declined fillet lipid content Jeong et al (2022) Superworm larvae ( Zophobas morio ) Meal Nile tilapia 3.00 ± 0.2 12 wk 15 Enhanced innate immune parameters (thrombocytes and neutrophils), liver and serum lysozyme activity, and complement system activity Alves et al.…”
Section: Utilization In Aquafeedsmentioning
confidence: 99%